ORP2, a cholesterol transporter, regulates angiogenic signaling in endothelial cells. Issue 11 (10th September 2020) - Koponen, Annika; Pan, Guoping; Kivelä, Annukka M.; Ralko, Arthur; Taskinen, Juuso H.; Arora, Amita; Kosonen, Riikka; Kari, Otto K.; Ndika, Joseph; Ikonen, Elina; Cho, Wonhwa; Yan, Daoguang; et al.
Abstract: Oxysterol‐binding protein‐related protein 2 (ORP2), a cholesterol‐PI(4, 5)P2 countercurrent transporter, was recently identified as a novel regulator of plasma membrane (PM) cholesterol and PI(4, 5)P2 content in HeLa cells. Here, we investigate the role of ORP2 in endothelial cell (EC) cholesterol and PI(4, 5)P2 distribution, angiogenic signaling, and angiogenesis. We show that ORP2 knock‐down modifies the distribution of cholesterol accessible to a D4H probe, between late endosomes and the PM. Depletion of ORP2 from ECs inhibits their angiogenic tube formation capacity, alters the gene expression of angiogenic signaling pathways such as VEGFR2, Akt, mTOR, eNOS, and Notch, and reduces EC migration, proliferation, and cell viability. We show that ORP2 regulates the integrity of VEGFR2 at the PM in a cholesterol‐dependent manner, the depletion of ORP2 resulting in proteolytic cleavage by matrix metalloproteinases, and reduced activity of VEGFR2 and its downstream signaling. We demonstrate that ORP2 depletion increases the PM PI(4, 5)P2 coincident with altered F‐actin morphology, and reduces both VEGFR2 and cholesterol in buoyant raft membranes. Moreover, ORP2 knock‐down suppresses the expression of the lipid raft‐associated proteins VE‐cadherin and caveolin‐1. Analysis of the retinal microvasculature in ORP2 knock‐out mice generated during this study demonstrates the subtle alterations of morphology characterized by reduced vessel length and increased density of tip cells and perpendicular sprouts. Gene expression changes in the retina suggest disturbance of sterol homeostasis, downregulation of VE‐cadherin, and a putative disturbance of Notch signaling. Our data identifies ORP2 as a novel regulator of EC cholesterol and PI(4, 5)P2 homeostasis and cholesterol‐dependent angiogenic signaling.